Knowledge and Awareness regarding Strabismus and Amblyopia among School Nurses and Primary School Teachers of Government Schools at Bharatpur - Shrestha, Manisha (Journal of College of Medical Sciences-Nepal, 2023)
Background Strabismus/squint is an ocular misalignment in which the eyes are not properly aligned with each other. Amblyopia is a serious visual impairment resulting from abnormal visual stimulation during early childhood. It can be easily prevented or treated if detected early. This study aimed to assess the knowledge and attitude of school nurses and primary school teachers of Government schools toward children suffering from strabismus and amblyopia. Method This was a cross-sectional study among the participating school nurses and primary school teachers of Government school which was organized to raise awareness regarding strabismus and amblyopia among them. It was conducted using a questionnaire which contained 22 items divided into three sections. First section consisted of demographic parameters, second regarding knowledge of strabismus and the third the knowledge of Amblyopia. Data were analysed using Epi info version 7.02 (Centers for Disease Control, Atlanta, Georgia, United States). P-values of <0.05 was used for clinical significance. Result There were 67 participants and the mean age was 32.67±7.71 years, range 21 to 55 years, the majority being female 66 (98.51%). Training on eye health was received by 13 (19.40%). Forty-four (65.67%) participants had knowledge of strabismus and amblyopia, out of them 30 were school nurses. The majority of school nurses 23 (76.67%) and primary teachers 13 (92.86%) had good knowledge scores (6 to 10). Conclusion The majority of participants had good knowledge about strabismus and amblyopia. As the school nurses and primary school teachers are the first link to the children at risk, improving their awareness level on strabismus and amblyopia will help in early referral, timely intervention and prevent the risk of vision loss.